Three-point functions in superstring theory on AdS 3×S 3×T 4 - Cardona, C.A. (2009)
We consider R and NS spectral flow sectors of type IIB superstring theory on AdS 3 × S 3 × T 4 in the context of the AdS 3/CFT 2 correspondence. We present a derivation of the vertex operators creating spectral flow images of chiral primary states previously proposed in the literature. We compute spectral flow conserving three-point functions involving these operators on the sphere. Using the bulk-to-boundary dictionary, we compare the results with the corresponding correlators in the dual conformal field theory, the symmetric product orbifold of T 4. In the limit of small string coupling, agreement is found in all the cases considered. © SISSA 2009.